2016
DOI: 10.15304/ie.26.3256
|View full text |Cite
|
Sign up to set email alerts
|

Competencias en TIC del profesorado en Galicia: variables que inciden en las necesidades formativas.

Abstract: La integración de las TIC en el aula requiere, entre otros factores, que el profesorado disponga de las competencias necesarias para su uso técnico, didáctico, y diseño de materiales y escenarios educativos que le permitan individualizar y flexibilizar la enseñanza. Sin embargo, estudios previos han puesto de manifiesto la existencia de carencias formativas en el profesorado para utilizar las TIC como recurso educativo. Los objetivos del presente trabajo consistieron en comprobar el grado de adquisición de hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…7 Total Digital Competence older teachers had lower ICT training than those who are younger. For example, in the dimension use of digital resources (B), male teachers over 40 have higher scores than those under 40, so there is a positive correlation with age ranges in management technical and instrumental of these digital resources by teachers, statements contradictory to those of Fernádez dela et al (2016) and López et al (2019) who also stated that younger teachers had a higher level of instrumental skills. Perhaps a possible explanation for why these areas have a higher competence profile is due to the type of knowledge they teach.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…7 Total Digital Competence older teachers had lower ICT training than those who are younger. For example, in the dimension use of digital resources (B), male teachers over 40 have higher scores than those under 40, so there is a positive correlation with age ranges in management technical and instrumental of these digital resources by teachers, statements contradictory to those of Fernádez dela et al (2016) and López et al (2019) who also stated that younger teachers had a higher level of instrumental skills. Perhaps a possible explanation for why these areas have a higher competence profile is due to the type of knowledge they teach.…”
Section: Discussionmentioning
confidence: 97%
“…It was verified that only 18 items of the 22 were grouped as a function of the theoretical dimension of belonging where they had to remain, with a rotation conversion of 20 iterations. Those items with factorial weights less than 0.3 were eliminated, as recommended by Henson and Roberts (2006). The maximum likelihood Oblimin rotation revealed the presence of six factors, which explained 71.22% of the variance.…”
Section: Psychometric Properties Of the Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the stage of Vocational Training, which is what we are dealing with in this article, few studies have been found, although Fernandez de la Iglesia [22] provides that vocational training teachers stand out about the other formative stages in the level of digital skills.…”
Section: Factors Influencing Teacher's Digital Competencementioning
confidence: 97%
“…Tras la situación vivida, el profesorado ha sido consciente de todas las herramientas y posibilidades didácticas que previamente desconocía, y a consecuencia de ello, su percepción sobre su CDD ha disminuido (Sánchez, 2020). En este sentido, además de reiterar los efectos y limitaciones de las evaluaciones basadas en la autopercepción anteriormente mencionados, sería necesario explorar otros factores de carácter psicosocial, como la actitud hacia las TD (Fernández et al, 2016), o tecnofobias asociadas al género (Castaño, 2008).…”
Section: Discussionunclassified